1994
DOI: 10.1007/bf02259674
|View full text |Cite
|
Sign up to set email alerts
|

Noncognitive factors in high-road/low-road learning: I. Modes of abstraction in adulthood

Abstract: Since the terms cognition and cognitive are broadly used but not clearly defined, it may be helpful to clarify what is meant by noncognitive factors. In cognitive science, the terms cognition and cognitive generally describe mental processes that are informational insofar as they carry information about the organism's own body and the material world. Thus defined, there are three sorts of noncognitive organismic factors important in adult learning: affective processes, self-developmental processes, and hardwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…1989: 1991b: Pascual-Leone and Goodman. 1979: Pascual-Leone and Irwin. 1994, Two of these are content learning (C learning) and logical-structural or pat terned learning (/.…”
Section: A Constructivist Dialectical Theory Of Learning and Developmentioning
confidence: 99%
See 1 more Smart Citation
“…1989: 1991b: Pascual-Leone and Goodman. 1979: Pascual-Leone and Irwin. 1994, Two of these are content learning (C learning) and logical-structural or pat terned learning (/.…”
Section: A Constructivist Dialectical Theory Of Learning and Developmentioning
confidence: 99%
“…We : Pascual-Leone and Goodman. 1979: Pascual-Leone and Irwin. 1994] refer to such learn ing as l.M learning, because mental attentional capacity (M 'energy') must be used to boost into hyperactivation the symbol's constituent schemes.…”
Section: Lm/symbolic Versus Lc/signauc Modes O F Learningmentioning
confidence: 99%
“…Finally, with the achievement of the Integrated level, both change and difference are valued; the ego is more permeable and less controlling of internal processes but is also at the same time more committed to its values and choices, however nonabsolute they may be, because they reflect more internal and organismic aspects of our selves. The distinction between the Intersystemic and the Integrated levels seems parallel to Pascual-Leone and Irwin's (1994aIrwin's ( , 1994b distinction between the predialectical and dialectical periods.…”
Section: Changes In the Vertical Organization Of Egomentioning
confidence: 85%
“…Psychological and organismic processes can be combined with social norms and canonical life scripts in a dialectical synthesis that enables truly innovative life choices and structures. In the model of ego of Pascual-Leone and Irwin (1994aIrwin ( , 1994b, the Ethos comes to predominate in its control of metaexecutive processes. The Ethos is that repertoire of ego schemes which is synthesized out of the schemes of the Passions and the Communion repertoires in dialectical interaction with projects, ego ideals, values and goals (the Ego-Milieu).…”
Section: Changes In the Vertical Organization Of Egomentioning
confidence: 99%
“…According to Piaget, to re-equilibrate individuals must assimilate (adjust information to fit current schema), accommodate (adjust schema to fit new information), or develop a new schema. In these studies and others it has been suggested that adjusting schematic structure, or accommodation, requires more mental effort and concentration (Pascual -Leone & Irwin, 1994;Piaget, 1977;Rumelhart, 1980;Rumelhart & Norman, 1978;Wadsworth, 1984).…”
Section: Introductionmentioning
confidence: 97%